Synthesis of renewable copolyacetals with tunable degradation - Rajput, Bhausaheb S.; Chander, Umesh; Arole, Kailash; Stempfle, Florian; Menon, Shamal K.; Mecking, Stefan; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2016)
Acetal metathesis copolymerization (AMCP) of renewable isohexide diacetals and aliphatic long-chain diacetals is reported and access to a small family of copolyacetals has been established. Crucial 1-2D NMR and MALDI-ToF-MS findings unambiguously confirm the existence of a copolymeric structure. In a stark contrast to the earlier reported isohexide-polyacetals, the current copolyacetals reveal very slow degradation. Hydrolytic degradation of copolyacetal pellets is extremely slow at pH 7, whereas only 30% degradation over a period of 15 d is observed in 9 M hydrochloric acid solution. GPC investigations reveal that with increasing chain-length the rate of degradation reduces, whereas copolyacetals with short-chain aliphatic segments display a faster degradation profile. The reduced rate of degradation can be attributed to the hydrophobic nature of long-chain acetal segments. In situ NMR spectroscopy reveals the existence of formates, hemiacetals, and diols as degradation products. Thus, the rate of degradation can be tuned by the judicious choice of isohexide-diacetal and linear-diacetals in a copolyacetal.
Keywords: copolyacetals; degradable polymers; diacetals; isohexides; renewable polymers

Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers